Dynamics of heavy metal uptake and soil heavy metal stocks across a series of Masson pine plantations. (1st October 2020) - Li, Hansen; Jiang, Long; You, Chengming; Tan, Bo; Yang, Wanqin
Abstract: To evaluate the roles of the plantations in cleaning soil heavy metals, the concentrations of copper (Cu), manganese (Mn), lead (Pb) and zinc (Zn) in both plant tissues and soils were therefore measured in the young (5a), half-mature (15a), near-mature (21a) and mature (27a) Masson pine ( Pinus massoniana ) plantations, and their stocks were further calculated. The concentrations of heavy metals varied with stand ages and tissues. The highest concentrations of Pb, Zn and Cu in pines were found in the half-mature plantation, while the highest value of Mn was found in the near-mature plantation. The concentrations and bioconcentration factors (BCFs) of Cu and Pb in pine tissues followed the order of root > need > branch > bark > trunk, and those of Mn and Zn followed the order of need > branch > bark > bark > root > trunk. Cu, Mn, Pb and Zn were stored mainly in the trunk, and the highest stocks of plants were found in the near-mature plantation. Although the concentrations and stocks of heavy metals in soils were not decreased with stand ages, the sustainable phytoextraction of Masson pine for heavy metals as affected by huge biomass and large planting area made Masson pine plantations play a positive role in cleaning soil heavy metals in non-point source pollution regions. Accordingly, it is highly recommended to log the near-mature Masson pine plantation to maximize the benefits of cleaning soil heavy metals and timber income. Highlights: Higher heavy metal stocks in plant tissues were observed in the near-mature or half-mature Masson pine plantations. Heavy metals were stored mainly in woody tissues, and timely timber harvest can clean lightly-polluted soils. Planting Masson pine is not an ideal measure for remediating heavily-polluted soil. Logging the near-mature plantation can maximize the benefits of cleaning soil heavy metals and timber income.